A decadal review of organizational identification: insights from bibliometric analysis and content analysis - Divya S; B. Prabu Christopher (Humanities & Social Sciences Communications)
Abstract In the face of global competition, it is imperative to conduct research on organizational identification in order to maximize employee commitment and organizational loyalty. Understanding how employees identify with their organizations can lead to improved productivity and retention rates. Organizational identification (OI) refers to an individual’s cognitive and affective connection to an organization. It exerts a significant impact on employee attitudes, behaviors, and job performance. It indicates an employee’s emotional bond, connectivity, and recognition with their company. This study aims to examine the impact of OI using bibliometric analysis and a literature review. Despite the topic’s wide use and coverage, the literature lacks quantitative data for bibliographic element analysis, making this study unique. This research fills that knowledge gap. We selected 227 research publications from the ABDC’s 2022 Quality Journals list, with A*, A, and B category journals for 2013 and 2022. The research methodologies employed encompassed trend analysis, scientific mapping, bibliographic coupling, co-occurrence analysis, and so on. Also, this study provides in-depth thematic analysis, content analysis, and a theoretical framework that contributes to the originality of the research. Our research findings offer bibliographic insights that enhance the study of literature. The study found that top journals are more interested in this topic. “Journal of Business Ethics” is very productive, whereas “Academy of Management Journal” holds the most influence. The study also highlights research gaps through quantitative and qualitative research. The study concluded by proposing further investigation and examining the consequences of its findings.